Analysis Of Vitamin D Levels in The Population Infected with Covid-19 - Yunita Sari; Dessy Hermawan; Nova Muhani; Syafik Arisandi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The global pandemic of covid-19 is a problem faced by all nations in the world and until now there has not been found a drug that is truly capable of killing the covid-19 virus. Yet the death toll continues to fall around the world. Until the middle of August 2022, more than 150 thousand people have died from this disease in Indonesia. The vaccination program also has not reached 70%, therefore one alternative way that can be done by society is to avoid being exposed to the covid-19 by implementing health protocols and maintaining/ increasing body resistance. Recently, there have been studies reporting that there is a relationship between vitamin D levels in the blood and the immune system. This study aims to analyze the relationship between vitamin D levels in the blood and a history of being infected with COVID-19. This was an analytical survey study with a cross-sectional approach that examines the relationship between blood vitamin D/25(OH)D3 levels, vaccine completeness status, adherence to the 5M health protocol, age and gender with a history of being infected with COVID-19. The population in this study was all lecturers at Malahayati University Bandar Lampung, totaling 303 people, while the sample was 62 Malahayati University lecturers willing to be sampled. The sampling technique used was non-probability sampling: consecutive sampling. The collected data were analyzed using logistic regression. The results showed that there was a relationship between adherence to health protocols (pValue: 0.007) with OR 6.48 (95% CI: 1.67 – 15.4) and vitamin D levels in the blood (pValue: 0.045) with OR 3.13 (CI95%: 1.02 – 9.59). The more disobedient to the procedure and the lower the level of vitamin D in the blood can impact the greater the potential for infection with COVID-19. There is a need for continuous education to remind the importance of implementing health protocols and the need to increase the intake of vitamin D either from food or from pro-vitamin D biosynthesis in the skin with ultraviolet B/UVB.